A History of Aging in Qing China - Ho, Clara Wing-chung. author. (orcid)0000-0003-0039-9990 Link aut Link
XVI, 207 p. 23 illus., 5 illus. in color.
Keywords: This book examines the history of aging and old age during the Qing dynasty, a pivotal period marked by rapid population growth that resulted in the largest elderly population in imperial China. Drawing on previously overlooked first-person accounts from the extensive collections authored by Qing men and women, it offers an overview of the self-curated collective aging journeys of several hundreds of elders. By centering the voices of individuals reflecting on their aging experiences, this book delves into the personal narratives from both genders, rediscovering their aging journeys, revealing their subjectively constructed emotional landscapes, and giving a voice to the elderly individuals of the past. The chapters closely analyze how the elderly in Qing China articulated their aging process, channeling their joys, challenges, and frustrations in later life. History is not the monopoly of a single gender, class, race, or age group; without representations of the elderly, history remains incomplete. This book seeks to restore the elderly to the historical narrative and invites further discussion on Chinese historical gerontology as an emerging subfield. In addition to appealing to general readers interested in contemporary demographic issues from a historical perspective, this book will engage students and researchers of history, historical gerontology, aging studies, gender studies, cultural studies, sociology, psychology, and Asian studies.